Prevalence of Intestinal Schistosomiasis and Associated Factors among School Children in Wondo District, Ethiopia - Mustafa Geleto Ansha; Kemal Ahmed Kuti; Ephrem Girma (Journal of Tropical Medicine)
Background. Human schistosomiasis is one of the neglected tropical diseases caused by Schistosoma mansoni. Children in the developing countries live in areas with poor sanitation and most often spend time swimming or bathing in the water bodies contaminated with cercariae, the infective stages of schistosomiasis, which results in growth retardation and poor school performance. Thus, having effective control of the disease requires assessment of prevalence and risk factors. Objective. This study was aimed at assessing the prevalence of S. mansoni and its associated factors among primary schoolchildren in Wondo district, West Arsi Zone, Ethiopia, 2018. Methods. A cross-sectional study was carried out between January and March 2018. Stool samples from 298 schoolchildren, who were selected by simple random sampling, were examined for the ova of S. mansoni using Kato–Katz technique. Information on sociodemographic factors and other risk factors was obtained using questionnaires. The data were cleaned, coded, and entered into SPSS 22.0 statistical software and analyzed. Bivariable and multivariable logistic regression analysis was done to identify factors associated with S. mansoni infection. Adjusted odds ratio (AOR) with 95% confidence interval (CI) was calculated, and the level of significance was declared at p values of less than 0.05. The result was presented using tables, figures, and text form. Result. A total of 298 study participants were involved in this study resulting in a response rate of 96.4% (298/309). The prevalence of S. mansoni infection was 11.4% (34/298). The prevalence was 8% (12/140) among males while it was 13% (22/158) among females. Swimming in rivers or ponds (AOR: 9.592; 95% CI: 1.972–46.655; P=0.005), latrine availability at household level (AOR: 0.075; 95% CI: 0.13–0.422; P=0.003), and awareness about schistosomiasis (AOR: 0.058; 95% CI: 0.004–0.409; P=0.007) were the factors independently associated with S. mansoni infection at p value < 0.05. Conclusion. The prevalence of S. mansoni was moderate as per the World Health Organization standard, since it was in the range of 10%–50%. This implies that schistosomiasis is still among major health problems. Thus, intensified effort is needed to address risk factors contributing to infection and control disease. Additionally, biannual mass drug administration with praziquantel is required according to the WHO standard.